Left Ventricular Myocardial Deformation Parameters Are Affected by Coronary Slow Flow Phenomenon: A Study of Speckle Tracking Echocardiography. Issue 5 (14th December 2015) - Gulel, Okan; Akcay, Murat; Soylu, Korhan; Aksan, Gokhan; Yuksel, Serkan; Zengin, Halit; Meric, Murat; Sahin, Mahmut
Abstract : Background: The coronary slow flow phenomenon (CSFP) is defined as a delayed distal vessel contrast opacification in the absence of obstructive epicardial coronary artery disease during coronary angiography. There is conflicting data in medical literature regarding the effects of CSFP on the left ventricular functions assessed by conventional echocardiography or tissue Doppler imaging. Therefore, we aimed to evaluate whether there is any abnormality in the myocardial deformation parameters (strain, strain rate (SR), rotation, twist) of the left ventricle obtained by speckle tracking echocardiography (STE) in patients with CSFP. Methods: Twenty patients with CSFP were included prospectively in the study. Another 20 patients with similar demographics and cardiovascular risk factors as well as normal coronary angiography were used as the control group. Two‐dimensional echocardiographic images of the left ventricle from the apical long‐axis, two‐chamber, four‐chamber, and parasternal short‐axis views were used for STE analysis. Results: The analysis of left ventricular circumferential deformation parameters showed that the averaged peak systolic strain, systolic SR, and early diastolic SR values were significantly lower in patients with CSFP (P = 0.009, P = 0.02, and P = 0.02, respectively). Among the left ventricular rotation and twist values, apical rotation was significantly lower in patients with CSFP (P = 0.02). Further, the mean thrombolysis in myocardial infarction frame count value was found to be negatively correlated with the averaged peak circumferential early diastolic SR (r = −0.35, P = 0.03). It was positively correlated with the averaged peak circumferential systolic strain (r = 0.47, P = 0.003) and circumferential systolic SR (r = 0.46, P = 0.005). Conclusion: Coronary slow flow phenomenon leads to significant alterations in the myocardial deformation parameters of the left ventricle as assessed by STE. Specifically, circumferential deformation parameters are affected in CSFP patients.